Perbandingan Kinerja Protokol DSDV dan FSR Terhadap Model Node Tetap dan Node Bergerak - Moh Irfan Haris; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
MANET is a well-known self-configuring and infrastructure-less network. Each device connected to MANET is called a node, each of which has different characteristics in terms of mobility, which plays a role in the quality of a network. A node, when conveying a packet, requires routing process as a mechanism to determine the best path to let it reach its right destination. This research focused on comparing the performances of DSDV and FSR routing protocols when applied to both fixed and mobile nodes by testing three parameters, namely Routing Overhead, End-to-end Delay, and Convergence Time. Test scenarios were performed by varying the number of both moving nodes and non-moving nodes and varying the size of the packet conveyed. The results showed that the FSR protocol is more suitable to be applied in large-scale networks, with the values of convergence time, end to end delay, and routing overhead of 0.118 sec, 20.813 ms, and 22.748, respectively. Meanwhile, DSDV protocol is more suitable to be applied in small-scale networks, with the values of convergence time, end to end delay, and routing overhead of 0.1 sec, 31.607 ms, and 8.875, respectively. The results also indicated that the greater the packet conveyed the more significant the effect on the performance of a network because the data needs to be broken down into several segments, which are vulnerable to failure (Packet Loss).